THE INFLUENCE OF FACILITIES, INFRASTRUCTURE, AND OPERATIONAL COSTS ON REVENUE (CASE STUDY OF PERUMDA MUARA TIRTA, GORONTALO CITY) - Rahmatiya Abdullah; Mattoasi Mattoasi; Ayu Rakhma Wuryandini (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study is to analyze the influence of facilities and infrastructure and operational costs on the revenue of Perumda Muara Tirta, Gorontalo City. This study uses a descriptive quantitative research design. The study population was 73 respondents with a questionnaire instrument. The results show that facilities and infrastructure affect revenue, and operational costs affect revenue. The coefficient of determination (R²) shows that both independent variables are able to explain variations in revenue substantially. This finding indicates that improving the quality of facilities and infrastructure and operational cost efficiency can increase company revenue. Perumda Muara Tirta management is expected to focus more on infrastructure management and operational cost control to maintain sustainable financial performance.